Community-Based Health Information System Governance Structural Mechanism: Its Role in Attaining the Alignment and Improving the Community Health Outcomes - Chumba, Hosea Kipkemboi; Waema, Timothy Mwololo; Ochieng, Daniel Orwa (Journal of Health Informatics in Africa, 2026)
Purpose - Health Information Technology (HIT) governance is necessary for the effective functioning of HIT systems to improve health outcomes. However, practices associated with the Community-Based Health Information System (CBHIS) governance structural mechanism remain unclear. In addition, there is a paucity of knowledge on the nature of the interrelationships between the CBHIS governance structural mechanism, alignment and community health outcomes. The study sought to establish and validate practices associated with the CBHIS governance structural mechanism and its interrelationships with community health-CBHIS alignment and community health outcomes. Methodology - This study employed a mixed-method research approach, utilising a convergent parallel research design. Two study sites were purposefully chosen from a total of 47 counties due to their experience in CBHIS implementation and use. A sample size of 179 respondents participated in the study. To analyse research data, the study used partial least squares (PLS) structural equation modelling (SEM). Findings - The study had eight different practices associated with the CBHIS governance structural mechanism construct and six indicators measuring community health outcomes. Reliability and validity of constructs were used to assess the measurement model. Cronbach’s alpha and composite reliability were utilised and study findings reveal that all the indicators met thresholds. In addition, the convergent validities for the two constructs were above the minimum threshold of 0.5000 (AVE>0.5000). Furthermore, the two constructs in this study met the discriminant validity criterion assessed using three techniques namely the Fornell-Lacker Criterion, HTMT and cross-loadings. The assessment of the structural model reveals a positive and significant relationship between the CBHIS structural mechanism and community health outcomes. The linkage between the CBHIS governance structural mechanism and community health outcomes have a Beta coefficient (β) of 0.507 (original sample) and 0.521 (bootstrap sample). The T statistic (t) is 7.159***. In addition, the positive relationship is highly significant at a P-value (p) 0.000. Furthermore, the coefficient of determination (R2) is 0.257. In addition, the study findings reveal a predictive relevance (Q2) of 0.224 (22.4%) of the exogenous construct on the endogenous construct. The study concludes that the model has an overall predictive relevance. Practical implications – The study findings reveal the practices associated with the CBHIS governance structural mechanism necessary for community health-CBHIS alignment to occur and consequently translate to improved community health outcomes. Keywords: Alignment, Governance structural mechanism, Health Information Technology